Comparative study of acute kidney injury in pararenal aortic aneurysm: open surgical versus endovascular repair - Sultan, Sherif; Acharya, Yogesh; Tawfick, Wael; Wijns, William; Soliman, Osama (Frontiers in Surgery, 2024)
BackgroundPararenal abdominal aortic aneurysms (PR-AAA), constituting around 15%-20% of AAA patients, are defined as having no neck between the aneurysm and the renal arteries. Due to an insufficient sealing zone, open surgical repair (OSR) is the gold standard, while EVAR is reserved for those unfit for surgery. Renal outcomes disturb long-term survival, and they have massive socioeconomic and quality of life implications, especially if patients require dialysis.MethodsThis study aims to elucidate any difference between EVAR and OSR of PR-AAA, excluding suprarenal aneurysms, with specific emphasis on renal dysfunction over the short and long term. An existing database of PR-AAA between 2002 and 2023 was used to glean information regarding the therapeutic option used. Renal events were defined by the RIFLE criteria. Out of 1,563 aortic interventions, we identified 179 PR-AAA, of which 99 high-risk patients had an aortic neck of less than 10 mm with complete follow-up. We excluded patients with fenestrated EVAR (FEVAR), branched EVAR (BEVAR), or chimney EVAR (Ch-EVAR) and any patients requiring visceral artery reimplantation.ResultsIn total, 63 patients underwent EVAR, and 36 required OSR. 17.46% of patients who underwent EVAR experienced acute kidney injury (AKI) compared with 36.11% of the OSR group (P = 0.037). The mean post-op creatinine for OSR was 109.88 µmol/L, and for EVAR was 127.06 µmol/L (P = 0.192). The mean difference between long-term (9–12 years) creatinine values in OSR was 14.29 µmol/L (P = 0.191), and the mean difference for EVAR was 25.05 µmol/L (P = 0.024). Furthermore, 27.8% of OSR patients who underwent Left Renal Vein Division and Ligation (LRVDL) experienced an AKI, while 50% who did not undergo LRVDL experienced an AKI (P = 0.382). Thirty-day morbidity in the EVAR group (20.97%) was significantly lower than in the OSR group (42.62%) (P = 0.022). Moreover, 3.17% in EVAR group and 7.14% in OSR group had aneurysm-related mortality (P = 0.584).ConclusionThe rate of renal events for OSR is higher, while the rate of endovascular renal events was lower. Our study shows that PR-AAA undergoing OSR may benefit from endovascular repair.